Strategy for Implementation of Carrageenan Quality Assurance System through ISO 9001:2015, HACCP and HrACCP - Noor Harini; Adi Sutanto; Dwi Okta Indriani; Wahid Muhammad Shodiq (Agriecobis : Journal of Agricultural Socioeconomics and Business, 2022)
The research objective is to find out the preparation, implementation and evaluation of ISO 9001 2015 certification, Food Safety with HACCP and Halal Assurance System with HrACCP at PT. Galic Bina Mada. The data analysis used is descriptive qualitative, namely analyzing data in the form of data reduction, data presentation, conclusion drawing and verification. The results show that the preparation of ISO 9001 2015 certification, Food Safety with HACCP and Halal Assurance System with HrACCP at PT. Galic Bina Mada was categorized as good. This is indicated by the completeness of all documents and the sequence of steps taken to obtain certification. The implementation of the ISO 9001:2015 quality assurance system, HACCP, HrACCP at PT. Galic Bina Mada showed a good or appropriate result, which was indicated by achieving the standard of achievement to document completeness. The implementation of the quality assurance system at PT. Galic Bina Mada could increase the number of production and improve product quality (kappa carrageenan grade). The results of the evaluation which included internal and external audits provided assurance of the achievement of the quality standard system. Suggestions that the authors can give are for PT Galic Bina Mada to make continuous improvements to ensure the operation of an effective quality management system and for future researchers to conduct further research for the running of the HACCP system at PT. Galic Bina Mada Pasuruan, after the certification process.